2009
DOI: 10.1186/1478-7954-7-9
|View full text |Cite
|
Sign up to set email alerts
|

The burden of disease and injury in Iran 2003

Abstract: The health and disease profile in Iran has made the transition from the dominance of communicable diseases to that of noncommunicable diseases and road traffic injuries. NBD results are to be used in health program planning, research, and resource allocation and generation policies and practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
244
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(264 citation statements)
references
References 8 publications
7
244
2
3
Order By: Relevance
“…4 DALYs lost per 1000 of the population in Iran. 3 Fifty-three percent of the total numbers of DALYs in Iran were in male patients, and 47% of DALYs were in female patients. 3 As expected, this study showed almost twice higher burden of SCI in male patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 DALYs lost per 1000 of the population in Iran. 3 Fifty-three percent of the total numbers of DALYs in Iran were in male patients, and 47% of DALYs were in female patients. 3 As expected, this study showed almost twice higher burden of SCI in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to a report from Iran in 2003, among disease groups, injuries has the highest burden of disease (DALY) which includes 28% of DALYF36.5% in male and 18% in female patients; and the first cause of years of life lost because of premature mortality (YLL). 3 Spinal trauma complicated by injury to the spinal cord is a devastating event on a personal and family level, as well as a tremendous financial burden to society because of its attendant morbidity, expense and prolonged treatment requirements. 4 Among all causes of injury-related morbidities, spinal cord injury (SCI) has one of the highest burdens because of permanent disability.…”
Section: Introductionmentioning
confidence: 99%
“…Less than 1% of breast cancer cases arise before 25 years of age but after 30, the incidence increases significantly and also increases with advancing the age (Jemal et al, 2009). Although the peak age of the onset for breast cancer is between 6th and 7th decades of the life worldwide, in Iranian population it seems that it is between 40 and 60 years of age (Naghavi et al, 2009). Most of the breast cancer cases are sporadic, however, a significant proportion are due to inheritance of particular genetic factors including mutations in specific genes (Fry-Johnson and Rowley, 2010 and Pichert, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, natural disasters contributed hugely to the disability-adjusted life-years (DALY) lost in Iran, being the second most important cause among male Iranians of all ages and the third most important among female Iranians (Naghavi et al, 2009). In the many earthquake-prone areas of the country, earthquakes may often have dramatic impacts not only on the epidemiology of many diseases (including CL, especially if it is already endemic) but also on healthcare (if the health infrastructure is severely damaged).…”
Section: Post-earthquake Cutaneous Leishmaniasis In Iranmentioning
confidence: 99%